Effect of «Osteogenon» on bone mineral density and dynamics of pain in patients with rheumatoid arthritis - Kuryata, Olexandr; Karavanska, Ilona; Lysunets, Tetyana; Garmish, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Rheumatoid arthritis ( RA) accompanied by extension of local (periarticular) osteopenia and of generalized bone loss. Patients with RA require prevention of osteoporosis the first basic drugs of which is calcium and vitamin D3. Objective: to evaluate bone mineral density (BMD) in patients with RA and dynamics of pain on the background of treatment with «Osteogenon» comparing with a combination of calcium / vitamin D. 47 patients with RA were divided into two groups. Patients of the first group obtained basic therapy and «Osteogenon», and of the second one — basic therapy and calcium with vitamin D. Results: pain decreased on 35,4 % (p < 0,05) and on 9,1 % (p < 0,05) in the first group and second one, respectively, after 6 months. BMD increased in patients of the first group on 4,13 % (p < 0,01) after 6 months, probable positive dynamics was not registered in patients of the second group. Significant increasing of BMD was observed in patients of the first group comparing with those who obtained standard combination of calcium carbonate with vitamin D at recommended doses.